Haemotological, biochemical and serum electrolyte changes in non-pregnant boer does inoculated with corynebacterium pseudotuberculosis via various routes - Othman, Abas Mazni; Abdullah, Faez Firdaus Jesse; Mohd Nordi, Nur Adza Rina; Ilyasu, Yusuf; Saad, Mohd Zamri; Haron, Abd Wahid; Saharee, Abdul Aziz; Mohd Lila, Mohd Azmi (International Organization of Scientific Research, 2014)
Caseous lymphadenitis is a chronic disease characterized by internal and external abscesses and is caused by Corynebacterium pseudotuberculosis.Thisstudy is designed to measure the hematological, biochemicaland serum electrolyte changes in experimental non-pregnant doesinoculated with Corynebacterium pseudotuberculosis via variousroutes. Little is known about the changes in these parameters through different routes of infection.A total of 20 healthy does (n=20) were divided into 4 groups (intradermal, intranasal, oral and control) of 5 goats each. The three groups were inoculated with 107cfu/1ml of live Corynebacterium pseudotuberculosis, while control is kept unexposed. Following infection, blood samples were collected from the jugular vein for hematological, biochemical and serum electrolyteanalysis. A significantdecrease was observed in RBC count (p<0.05) in the intradermal group, whilenochangesobserved in PCV, Hb, MCV and MCHC parameters. Significant increasein WBC were observed in intradermal, intranasal and oral groups (p<0.05). Slight increase (p<0.05) in monocyte count was observed in intranasal group. A significant reduction (p<0.05) in lymphocytic count was observed for the intranasally inoculated group (p<0.05) and a slight increase (p<0.05) in neutrophil was observed in intranasal and intradermal groups. Biochemically,creatinine and albumin levels increases inintranasal group(p<0.05) and GGT levels were elevated in all the three infected groups (p<0.05).However,there were no significant changes in AST, T.Protein and APT. Serumelectrolyte, revealed a decrease in Calcium (Ca+) concentration in intradermal group with concentration of 2.22mmol/L,intranasal 2.23mmol/L group (p<0.05), and no changes were observed in potassium (K+) and sodium (Na+). The study, therefore, observed increase in WBCs, neutrophils, monocytes, creatinine, GGT, albumin levels and decrease in RBCs, lymphocytes and calcium concentrations on different route of infections.